Exploring Social Media on Gender Identity Development Among Generation Z: A Discourse Analysis on Opportunities, Challenges, and Societal Tensions - Damayanti, Yulianingtyas Dwi; Ananda, Aulia Sagita; Rosalinah, Yanti (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study explores the impact of social media on the gender identity development of Generation Z, focusing on the opportunities and challenges these platforms present in shaping young people's understanding of gender. Generation Z, born between 1997 and 2012, is the first generation to grow up in an era of pervasive digital connectivity, where social media platforms offer unprecedented spaces for self-expression and identity exploration. These platforms enable young people to engage with diverse gender identities, including non-binary and gender-fluid expressions, which are often marginalized in offline spaces. However, while social media provides opportunities for authentic self-expression, it also amplifies societal pressures to conform to idealized gender norms. The tension between digital empowerment and offline societal expectations creates a complex environment for Generation Z, where they must navigate conflicting gender narratives. This study employs a descriptive qualitative approach, utilizing documentary analysis of social media content and academic literature to identify key themes related to gender identity formation, societal pressures, and the intersectionality of gender with cultural, social, and psychological factors. The findings suggest that, while social media plays a critical role in empowering young people to explore diverse gender expressions, it also exposes them to identity conflicts and psychological challenges, particularly when offline societal norms resist these new identities. The study calls for greater support systems, both online and offline, to help young people navigate these complexities and embrace their gender identities freely and authentically.